Detection of Pathogenic Leptospires in Rat and Shallow Populations and Its Spatial Distribution in Bakaran Kulon Village, Pati District - Dyah Widiastuti; Nova Pramestuti; Zumrotus Sholichah; Endang Setiani; Raden Ludhang P Rizki (Insights in Public Health Journal, 2021)
Background In tropical areas, Leptospirosis is still considered a public health problem, particularly in the event of heavy rainfall and flooding. Transmission of leptospira bacteria from infected animals, such as rats, takes place through the urine or blood. Different serovar leptospires can be found in different reservoir animals in the field. However, research on the presence of pathogenic leptospires in rats in Pati Regency, one of the areas with leptospirosis cases in Central Java, is very limited. Objectives: The purpose of this research is to identify Leptospira characteristics. Spp in rat and its distribution in Pati Regency. Methods: Rat capture was carried out in Bakaran Kulon Village in Pati Regency. Detection of pathogenic leptospires was carried out using the ropB gene and followed by phylogenetic analysis. As additional details, a buffer analysis was carried out to measure the distance between the positions of cases of leptospira and positive rats positions. Results: Pathogenic were found in 11.76% (2/17) of rats and shallows in the area of study. Based on DNA leptospires sequencing, Leptospira found in Bakaran Kulon Village Pati Regency were Leptospira interrogans serovar Bataviae and Leptospira borgpetersenii serovar Ballum, both of which are pathogenic. Based on a buffer analysis, Leptospira-positive rat was found around cases of leptospirosis at distances of 30 and 60 m. Conclusion: This study shows that Leptospira spp. in rats found around the location of leptospirosis cases, which indicates that rats have great potential as transmitters of leptospirosis to humans.